2010
DOI: 10.1007/s10953-010-9572-3
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Study on the Binding of Cobalt(II) and Iron(III) Ions with Bovine Carbonic Anhydrase II at Different Temperatures

Abstract: A thermodynamic study on the interaction of bovine carbonic anhydrase II, CAII, with cobalt(II) and iron(III) ions was made using isothermal titration calorimetry (ITC) at 300.15 K and 310.15 K in Tris buffer solutions at pH = 7.5. The enthalpies of interaction of Co 2+ + CAII and Fe 3+ + CAII are reported and analyzed in terms of the extended solvation theory. The results indicate that there are three identical and non-cooperative binding sites for Co 2+ and Fe 3+ ions. Binding of these ions with CAII occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Protein interactions with small ligands (including co‐factors and drugs) Protein/peptide interactions with metals and ions Protein/peptide interactions with nucleic acids …”
Section: Introductionmentioning
confidence: 99%
“…Protein interactions with small ligands (including co‐factors and drugs) Protein/peptide interactions with metals and ions Protein/peptide interactions with nucleic acids …”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously [4][5][6][7][8] that the heats of the macromolecules+ligands interactions in the aqueous solvent systems can be reproduced by the extended solvation model as follows:…”
Section: Resultsmentioning
confidence: 99%
“…There are two distinct sets of binding sites on lysozyme, which are clear in Figure 1. The dissociation equilibrium constant (K d ) and the number of binding sites "g" can be determined by the following equation [4][5][6][7][8] 0 0 The binding parameters recovered from Equations. 1, 5 and 6 were listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when Fe 3+ replaces the native Zn 2+ , it significantly enhances enzyme activity by modifying the enzymes by metal ion replacement. The complexes formed by Fe 3+ and CA also exhibit higher stability [55].…”
Section: Xps Analyses Of Biominerals Induced By Synechocystis Sp Pcc ...mentioning
confidence: 98%
“…Therefore, a sufficiently high concentration of Mg 2+ ions does indeed inhibit CA activity. It has been reported that CA is a metalloenzyme containing Zn 2+ at its biologically active sites, and this essential metal ion can be substituted with other metals such as Fe 3+ [55]. Interestingly, when Fe 3+ replaces the native Zn 2+ , it significantly enhances enzyme activity by modifying the enzymes by metal ion replacement.…”
Section: Xps Analyses Of Biominerals Induced By Synechocystis Sp Pcc ...mentioning
confidence: 99%